In vivo Analgesic activity of methanolic extract of Helianthus annuus seeds (International Current Pharmaceutical Journal, 2016)
The sunflower seed is the seed of the sunflower (Helianthus annuus). The methanol extract of seeds of Helianthus annuus were screened for analgesic activity in mice model to systematically explore the medicinal values of the plant. Acetic acid induced writhing and hot plate methods were used to confirm the central and peripheral analgesic action. In case of acetic acid-induced writhing test the extract showed significant (P